2019
DOI: 10.1016/j.cgh.2018.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of the Gut Microbiome in Nonalcoholic Fatty Liver Disease: From Composition to Function

Abstract: The gut microbiome, a diverse microbial community in the gastrointestinal tract, plays a pivotal role in the maintenance of health. The gut microbiome metabolizes dietary and host-derived molecules to produce bioactive metabolites, which have a wide array of effects on host metabolism and immunity. 'Dysbiosis' of the gut microbiome, commonly considered as perturbation of microbiome diversity and composition, has been associated with intestinal and extra-intestinal diseases, including nonalcoholic fatty liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 81 publications
(191 reference statements)
5
98
0
1
Order By: Relevance
“…Is this a valid overarching hypothesis to explain high levels of hepatic steatosis or an overreaching set of conclusions? In support of the authors’ hypothesis, previous studies have reported that the microbiome in NAFLD is different from obesity without NAFLD and that, among patients with biopsy‐proven NAFLD, the microbiome is different in those who have advanced fibrosis versus those with stage 0‐2 fibrosis, demonstrating a unique disease–microbiome association . Moreover, recent data from a twin study provide proof‐of‐concept data indicating a role of gut‐microbial metabolites (such as 3,4‐hydroxyphenyl lactate) in linking shared gene effects between liver fat and fibrosis in NAFLD .…”
supporting
confidence: 54%
“…Is this a valid overarching hypothesis to explain high levels of hepatic steatosis or an overreaching set of conclusions? In support of the authors’ hypothesis, previous studies have reported that the microbiome in NAFLD is different from obesity without NAFLD and that, among patients with biopsy‐proven NAFLD, the microbiome is different in those who have advanced fibrosis versus those with stage 0‐2 fibrosis, demonstrating a unique disease–microbiome association . Moreover, recent data from a twin study provide proof‐of‐concept data indicating a role of gut‐microbial metabolites (such as 3,4‐hydroxyphenyl lactate) in linking shared gene effects between liver fat and fibrosis in NAFLD .…”
supporting
confidence: 54%
“…This effect of metformin on gut microbiota supports its potential role in the treatment of NAFLD; preclinical studies have suggested a causal role of gut microbiota in NAFLD (reviewed in Sharpton et al) and there is a clear association between dysbiosis and NAFLD in humans. Additionally, progression of NAFLD in humans is associated with an overall decrease in microbial diversity in the gut . Metformin could therefore potentially reduce IHTAG through the gut‐liver axis and additionally prevent progression of NAFLD to more serious liver disease.…”
Section: Future Potential Of Metformin For Nafldmentioning
confidence: 66%
“…94,95 Additionally, the transfer of human fecal samples from metformin-treated individuals to germ-free mice improves glucose tolerance. 91 This effect of metformin on gut microbiota supports its potential role in the treatment of NAFLD; preclinical studies have suggested a causal role of gut microbiota in NAFLD (reviewed in Sharpton et al 96 ) and there is a clear association between dysbiosis and NAFLD in humans. Additionally, progression of NAFLD in humans is associated with an overall decrease in microbial diversity in the gut.…”
Section: Altering Gut Microbiomementioning
confidence: 89%
“…In this context, the intestinal microbiota (IM) was increasingly studied and a loss of intestinal microbiota diversity has been linked to disease severity. Also, IM regulates metabolism and inflammation through increased energy uptake, insulin sensitivity, and activation of the intestinal immune system . While inflammation is essential for disease progression, the strongest predictor of mortality in patients with NASH is hepatic fibrosis .…”
Section: Introductionmentioning
confidence: 99%